DIPLOMATIC ASYLUM AND THE ALAN GARCIA CASE - Peruana de Derecho Internacional, Sociedad (2020)
Diplomatic or political asylum is a relevant institution within the universalsystem of protection of human rights and fundamental freedoms. Although it is basicallyregulated in Latin America, there is also some practice in the rest of the world, even if inprinciple it is not granted legal recognition. In this sense, diplomatic asylum is acontribution made by Latin America, within the framework of International AmericanLaw, to International Human Rights and to International Law in general. Althoughdiplomatic asylum is granted on the grounds of political persecution, in the case of AlanGarcia, Uruguay has denied this asylum as there were no political crimes. The purposeof this article will be to introduce some basic concepts about diplomatic asylum and thecase of Alan Garcia, where it was denied asylum because it was an investigation forcommon crimes.